Evaluation of The Clinical Supervision to Clinical Rotation Students In a Faculty of Medicine - Irwan Ashari; Titi Savitri Prihatiningsih; Angela Nurini Agni (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: The clinical education at the Faculty of Medicine, University of Muhammadiyah Makassar, must be completed in four semesters. During that period, the students are educated and supervised by specialists or doctors on duty at the hospital. Since the first implementation of the clerkship clinical system at this university, evaluation on the implementation of clinical supervision provided by lecturers to the students for their clinical clinic had never been conducted. Therefore, it was necessary to evaluate the clinical supervision provided by the clinical instructor to the students for their clinical clerkship at FK-Unismuh. This study aims to evaluate the clinical supervision provided by lecturers to the clinical clerkship students at FK-Unismuh Makassar.Method: This study was a descriptive survey. The subjects were 123 clinical clerkship students of FK-Unismuh Makassar who had completed clinical rotation at the department of Internal Medicine, Pediatric, Surgery, and Obstetrics and Gynecology. The research subjects were grouped based on their clinical rotation that had been undertaken. The instruments used were the Clinical Teaching Effectiveness Instrument (CTEI) and the students’ log book for their clinical activities. The collected data were analyzed descriptively.Results: The effectiveness of clinical supervision showed that the overall average total score of CTEI was more than 3 with a range from 3.52 (internal medicine) to 3.84 (surgery). The lowest clinical supervision was at setting up a good time for both services and teaching (3.50). The average frequency of supervision received in Internal Medicine was 91.2 times. The average number of timely, late, and delayed supervision was 40 times (44%), 23 times (26%), and 28 times (30%), respectively. The average supervision duration of under 30 minutes, 30-60 minutes, and more than 60 minutes was 63 times (69%), 16 times (18%), and 12 times (13%), respectively.Conclusion: The effectiveness of the overall clinical supervision at 4 departments was rated ‘good’ by clerkship students. However, there were some items of the clinical supervision which were still undervalued by the students. At the Department of Internal Medicine, the number of students accepted uneven supervision, much clinical supervision was carried out not on time, and duration of supervision was inadequate.